Thermoelectric generation for waste heat recovery: Application of a system level design optimization approach via Taguchi method. (15th September 2018) - Ji, Dongxu; Wei, Zhongbao; Mazzoni, Stefano; Mengarelli, Marco; Rajoo, Srithar; Zhao, Jiyun; Pou, Josep; Romagnoli, Alessandro
Highlights: A framework based on Taguchi method is built to optimize thermoelectric generator. The simulation model is built and validated both in module level and system level. Five design parameters are studied in two different case. Influence of each design parameters on power output are quantified. Optimal design parameter combinations are suggested based on largest signal-to-noise ratio. Abstract: Thermoelectric generator is a solid-state energy converter which can convert waste heat directly into electricity. During the past decades, thermoelectric materials have been widely investigated whereas the integrated design of thermoelectric generators have been less studied. This paper proposes and implements a framework for the design of thermoelectric generators, consisting of thermoelectric modules and heat exchangers, based on the Taguchi method. As compared with previous researches which optimize the thermoelectric module alone and assume fixed temperature or fixed heat fluxes for the thermoelectric modules, this work proposes a methodology to optimize the thermoelectric module and the heat exchanger together. Five design parameters (namely the height, the fill-ratio, the ratio of cross-sectional area of n-type material over p-type material of thermoelectric module, the length and the material of the heat exchanger) were analyzed for two different applications, waste heat recovery from marine and automotive engines. In order to perform the analysis, a L27 (3 5 ) orthogonal array was employed to assess all of the design parameters returning the maximum output power. By analysis of variance, it is found that the thermoelectric module height is the most important design parameter contributing for the 69.6% and 30.25% in automotive and marine application, respectively. And the optimal design parameter set are also determined in both applications.